Frailty and quality of life in adult survivors of childhood cancer. Issue 2 (4th March 2017) - Ness, Kirsten; Howell, Carrie; Bjornard, Kari
ABSTRACT: Introduction : Adult survivors of childhood cancer are at risk for frailty, a state of diminished physiologic reserve, typically seen in older adults, associated with morbidity and mortality. They are also at risk for poor quality of life. This review explores potential associations between frailty and quality of life and proposes potential interventions that may prevent or remediate frail health. Areas covered : A literature search using MEDLINE and EMBASE was undertaken using key words: childhood cancer survivors and each of the following: frailty, physical performance, emotional health, and quality of life. 796 abstracts were reviewed for relevance. Reference lists for retrieved articles were consulted for pertinent manuscripts (N = 40). Recent literature (from January 2013 to November 2016) was obtained using the key words: aging and frailty and quality of life. The final reference list includes 44 documents. Expert commentary : Childhood cancer survivors are at risk for frailty and less than optimal quality of life. Poor emotional health may contribute to this association. Further research is needed to better explain these associations and to provide a foundation for the development of interventions designed to prevent and remediate frail health and suboptimal quality of life in this population.